ECONOMICS OF THE ADOPTION OF CLIMATE-SMART AGRICULTURAL PRACTICES AMONG SMALLHOLDER RICE FARMERS IN DUTSE, JIGAWA STATE, NIGERIA - Ahungwa, G. T.; Abdullahi, K. U.; Aker, E. I.; Gama, E. N. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the economics of adopting Climate-Smart Agricultural Practices among smallholder rice farmers in Dutse Local Government Area, Jigawa State, Nigeria. A multi-stage sampling technique was used in 131 smallholder rice farmers from the study area. Computer-Assisted Personal Interviews (CAPI) were used for data collection. The Principal Component Analysis (PCA) was employed to identify the climate-smart agriculture practices adopted by smallholder rice farmers. At the same time, the Benefit-Cost Ratio analysis was used to evaluate the economic viability of the adoption of CSAPs. PCA results showed a Cronbach’s Alpha coefficient of 0.915, a Kaiser-Meyer-Olkin of 0.869 and the Bartlett’s test of sphericity χ² (df) = 2500 (274), p<0.000. The PCA extracted five (5) uncorrelated factor components, involving 24 CSA practices: Climate-resilient rice cultivation (21.5%), Soil and land-based management (16.8%), Water and nutrient management (14.8%), Technological and diversification (10.7%), and Ecologically-friendly pest management (10.5%) of the total variation of CSAPs adoption patterns. Despite the initial high cost of adopting CSA, the Benefit-Cost analysis yielded a ratio of 3.03, an index of economic viability of the adoption of CSA. The study concludes that the adoption of climate-smart agricultural practices has significant economic viability for smallholder rice farmers in the study area. The study therefore recommended that improving access to credit, cooperative action, and scaling affordable water-saving technologies are the recommended pathways for enhancing climate-resilient rice production.